The Broodmother as Monstrous-Feminine: Abject Maternity in Video Games - Stang, Sarah (Nordlit, 2019)
This article examines examples of the monstrous-feminine in the form of abject maternal monsters in a selection of commercially successful and critically acclaimed mainstream video games using conceptual frameworks and textual analysis methods established in the work of Julia Kristeva and Barbara Creed. The Broodmother from Dragon Age: Origins (2009) and the Mother from Dragon Age: Origins—Awakening (2010) are considered as problematic examples of the abject monstrous-feminine which fall into a long tradition in horror media of framing the female body and the birthing process as something horrific and repulsive. Kerrigan from the StarCraft series (1998–2017) is examined as a possible counter-example, demonstrating that the monstrous-feminine can exist in a playable and potentially empowered form, though she is problematically empowered within a violent, militant framework. Overall, this article critically analyses the ways in which video games remediate tropes of gendered monstrosity and reinforce the misogynist norms and values of hegemonic heteropatriarchal ideology by forcing players to enact symbolic violence against transgressive female bodies.